Just how wide should 'wide reading' be?. (3rd June 2015) - Lipscomb, Martin
Abstract Educationalists introduce students to literature search strategies that, with rare exceptions, focus chiefly on the location of primary research reports and systematic reviews of those reports. These sources are, however, unlikely to adequately address the normative and/or metaphysical questions that nurses frequently and legitimately interest themselves in. To meet these interests, non‐research texts exploring normative and/or metaphysical topics might and perhaps should, in some situations, be deemed suitable search targets. This seems plausible and, moreover, students are encouraged to 'read widely'. Yet accepting this proposition creates significant difficulties. Specifically, if non‐research scholarly sources and artistic or literary (humanities) products dealing with normative/metaphysical issues were included in what are, at present, scientifically orientated searches, it is difficult to draw boundaries around what – if anything – is to be excluded. Engaging with this issue highlights problems with qualitative scholarship's designation as 'evidence'. Thus, absurdly, if qualitative scholarship's findings are labelled evidence because they generate practice‐relevant understanding/insight, then any literary or artistic artefact (e.g. a throwaway lifestyle magazine) that generates kindred understandings/insights is presumably also evidence? This conclusion is rejected and it is instead proposed that while artistic, literary, and qualitative inquiries can provide practitioners with powerful and stimulating non‐evidential understanding, these sources are not evidence as commonly conceived.